Temperature-dependent compatibility study on halide solid-state electrolytes in solid-state batteries - Jia, Gaoshuai; Deng, Zhi; Ni, Dixing; Ji, Zhaoran; Chen, Diancheng; Zhang, Xinxin; Wang, Tao; Li, Shuai; Zhao, Yusheng (Frontiers in Chemistry, 2022)
All-solid-state lithium batteries (ASSLBs) have attracted much attention as their high safety and energy density compared to conventional organic electrolyte. However, the interfaces between solid-state electrolytes (SSEs) and electrodes still face severe compatibility problems. Among many types of SSEs, halide SSEs exhibit relatively good interfacial compatibility. Herein, the temperature-dependent interfacial compatibility of halide SSEs in solid-state batteries are investigated by thermal analysis using simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), X-ray diffraction (XRD). Halide SSEs, including rock-salt type Li3InCl6 and anti-perovskite type Li2OHCl, show good thermal stability with oxides LiCoO2, LiMn2O4 and Li4Ti5O12 up to 320 ℃. Moreover, anti-perovskite type Li2OHCl shows a chemical reactivity with other battery materials (eg. LiFePO4, LiNi0.8Co0.1Mn0.1O2, Si-C and Li1.3Al0.3Ti1.7(PO4)3) at 320 ℃, which reaches the melting point of Li2OHCl. It indicates that Li2OHCl has relatively high chemical reactivity after melting. In contrast, rock-salt type Li3InCl6 shows higher stability and interfacial compatibility. This work delivers insights into the selection of suitable battery materials with good compatibility for ASSLBs.